Complex of test exercises: the key to success in children's sports - Pazdnikova N.P. ,; Opletin A.A. ,; Romanov V.V. ,; Maksimova A.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to create and demonstrate the efficacy of a set of assessment tasks for children, tailored to their developmental stage and aligned with their sensitive developmental period. Methods and structure of the study. The current phase of advancement in youth sports and the system of training sports reserves is marked by the rapid development of young athletes, with training loads that do not align with age-appropriate periodization, and a high level of expectations, which significantly affects their success and longevity in their careers, as well as the quality of their achievements. To address these issues, the authors suggest a testing approach that focuses on identifying the content and structural elements of children's physical activity, which is represented by a comprehensive set of eleven exercises. Results and conclusions. Following the evaluation of eight groups of participants, the researchers have determined that in the process of training athletes, the most crucial aspect is the implementation of carefully chosen training methods and the development of training programs that take into account the age-related characteristics, predispositions, and sensitive periods of young athletes. The effective selection of athletes, as well as the alignment of training programs and sports training systems with the sensitive periods and individual predispositions of young athletes, will contribute to the advancement of the country's sports reserve and the enhancement of the social image of the high-performance sports sector as a whole.